Patogenicidade de cepas de Brucella ovis isoladas de campo e avaliação da proteção induzida pela cepa vacinal encapsulada B. ovis ΔabcBA em camundongos - Thaynara Parente de Carvalho (2019)
Brucella ovis is responsible for economic and reproductive losses in sheep herds. The goal of this study was to characterize the infection with B. ovis field isolates in a murine model, and to evaluate protection induced by the B. ovis ΔabcBA vaccine strain in mice challenged with these field isolates. All field strains were able to colonize and cause lesions in the liver and spleen of infected mice. After an initial screening, two strains were selected for further characterization (B. ovis 94 AV and B. ovis 266 L). Both strains had an in vitro growth kinetics that was similar to the reference strain B. ovis ATCC 25840. Vaccination with Brucella ovis ΔabcBA encapsulated with 1% alginate was protective against the challenge with field strains of B. ovis, with the following protection indexes (log difference of bacterial loads in the spleen of vaccinated and non vaccinated mice): 0.751, 1.736, and 2.746, for mice challenged with B. ovis ATCC25840, B. ovis 94 AV, and B. ovis 266 L, respectively. In conclusion, these results demonstrated that B. ovis field strains were capable of infecting and inducing lesions in experimentally infected mice. The attenuated vaccine strain B. ovis ΔabcBA induced protection in mice challenged with different strains of B. ovis, including field isolates.